THE PUN-GROUP OF LINGUISTIC DEVICES IN ADVERTISING MEDIA DISCOURSE - Arakelyan, Hamlet (Armenian Folia Anglistika, 2021)
The language of advertising is unique and very peculiar in comparison with other elements of media discourse. The effectiveness of speech in advertising media discourse focuses on catching the attention of the target audience. Since the language of advertising is characterized by a distinguished persuasive function, the creators of ads spare no effort to make them catchy, interesting and witty. This is the reason why various linguistic devices are used to facilitate the comprehension and memorization of advertisements. In this regard, wordplay plays a significant role  as the intentional usage of puns ensures the effectiveness of the composed texts.
Keywords: advertising media discourse; linguistic devices; speech impact; wordplay; punnical devices